Determination of the elemental composition of aerosol by femtosecond laser-induced breakdown spectroscopy - Babushkin, P. A. (Atmospheric and oceanic optics)
For remote sensing of the aerosol atmosphere by femtosecond laser-induced breakdown spectroscopy (LIBS), it is necessary to choose an effective scheme based on the information about an angular distribution of emission from the filamentation domain. We present the results of a series of experiments on the identification of an impurity with the use of femtosecond LIBS. The angular distribution of the impurity emission from the femtosecond radiation filamentation domain in the atmosphere in the range from 0 to 180 degrees is estimated from the experimental data. A model of the angular distribution of the emission is suggested, where absorption in the filament plasma is taken into account. The variation in the emission line intensity with the impurity concentration is analyzed. It is shown that emission from the filamentation domain occurs due to spontaneous radiation.